2009
DOI: 10.1016/j.carbpol.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent-dependent viscoelastic properties of chitosan membranes on the permeation of 2-phenylethanol

Abstract: a b s t r a c tThe viscoelastic behaviour of chitosan was followed by dynamic mechanical analysis (DMA) while the sample was immersed in gradient compositions of water/ethanol mixtures. The swelling equilibrium of chitosan membranes, both crosslinked with genipin or not, increased linearly with the water content. Increasing the water content, it was simultaneously observed a peak in the loss factor (around 25 vol.%) and a reduction of the storage modulus, which was attributed to the a-relaxation of chitosan. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…For 0 vol% of water, pure ethanol, values of E′ of 0.35 GPa were found, which are very similar to the data found in dry chitosan [12], indicating that, at this composition of ethanol, CHT is in a glassy state. In a previous work, Caridade et al [13] reported that no absorption was detected for 100 vol% ethanol in swelling experiments. When water started to be introduced in the ethanol bath, the values of E′ decreased continuously.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 93%
See 2 more Smart Citations
“…For 0 vol% of water, pure ethanol, values of E′ of 0.35 GPa were found, which are very similar to the data found in dry chitosan [12], indicating that, at this composition of ethanol, CHT is in a glassy state. In a previous work, Caridade et al [13] reported that no absorption was detected for 100 vol% ethanol in swelling experiments. When water started to be introduced in the ethanol bath, the values of E′ decreased continuously.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 93%
“…This peak around 35 vol% is in accordance with the water content above which the Young's modulus reaches a plateau, mentioned before ( Figure 2). This peak is attributed to the glass transition (T g ) of chitosan, whereby it passes from a glass to rubber-like state transition that is induced by the entrance of water in the chitosan matrix [13]. Such water content can be seen as an external variable that may control the molecular mobility of the polymeric structure.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if a stress normal to the platelet plane is applied, a viscoelastic dissipative process will take place mainly in the hydrated state [2] and the ductile organic fraction that glues the crystals will prevent an uncontrolled crack growth [50]. Regarding the transition from a brittle (glassy) state to a more elastomeric behavior that occurs on nacre's hydration, a similar behavior was observed in chitosan using nonconventional dynamic mechanical analysis, in which glass transition could be detected in intermediate hydration levels [51,52]. Moreover, photoacoustic Fourier transform infrared spectroscopy results suggest that the water present at the nanograin interfaces also contributes significantly to the viscoelasticity of nacre [53,54].…”
Section: Why Is Nacre So Strong?mentioning
confidence: 65%
“…This viscoelastic dissipative process takes place mainly in the hydrated state, and dry nacre behaves very much similar to pure aragonite because the organic material becomes brittle (Barthelat 2007). The transition from a brittle (glassy) state to a more elastomeric behaviour was observed in a polysaccharide (chitosan) upon hydration using non-conventional dynamic mechanical analysis, in which a glass transition could be detected in intermediate hydration levels (Mano 2008;Caridade et al 2009). Photoacoustic Fourier transform infrared spectroscopy results suggest that the water present at the nanograin interfaces also contributes significantly to the viscoelasticity of nacre (Mohanty et al 2006;Verma et al 2006).…”
Section: Mechanical Performancementioning
confidence: 99%